З історії лексики української ділової мови (довіреність, доручення) - Боярчук, О. (Лексикографічний бюлетень, 2011)
Ukrainian official-business language lexis and phraseology is currently in the phase
of formation and unification. The article is dedicated to the issue of functioning of two
Ukrainian official-business language terms – довіреність and доручення. The usage of
these terms is still inexact. Thus this issue needs to be thoroughly studied. To study the
history of two aforementioned terms in the Ukrainian official-business language, we
appealed not only to contemporary interlingual official-business, law, and banking language
dictionaries, but also to the dictionaries published in Ukraine during the twentieth
century. To achieve the legal certainty in the usage of these terms in the meaning of
“a document by which somebody is granted power of attorney”, we should choose only
one of them. As far as the term доручення has a little bit different connotation and it is
an equivalent to the Russian lexeme “поручение”, the most optimal alternative may be
to leave the term довіреність.